К вопросу о происхождении названия «Борисфен» - Русяева, А.С. (Боспорские исследования, 2009)
Different scientific points of view about the etymology of the river Borustheues and the ancient polis of the same name have been surveyed in the article. The polis is the most ancient one in the north Pontic area. Being the unique monuments and a real gem of archaic culture of the Hellenoi it has not got its constant name yet. Undoubtedly, it needs radical re-examine and substitution of the name Berezan settlement (= Berezan), which prevails in modem science, to the original name Borusthenes.